STRATEGI PENINGKATAN EKSPOR PRODUK KELAUTAN DAN PERIKANAN KE PASAR EROPA - Ali Mursit; Agus Wahyono; Yuli Setiawan (Jurnal Manajemen, 2022)
Fishery resources produced amounted to 12.5 million tons/year with an economic value of $2.04 billion USD. From 2016 - 2020 Indonesia's fisheries export sector continues to experience a positive trend by continuing rises with an increase of 5.72% and in 2020 the value was reached of $5.205 billion USD. The export sector who dominates is with fishery products have code 0303, and fishery commodities types shrimp, tuna, skipjack, seaweed, squid-octopus, crabs, etc. There are several obstacles i.e strict on standards of trade rules in the EU, the absence of Indonesia's free trade agreement with the EU, producers that tend to change frequently and the low quality of fishermen's human resources and not yet in accordance with the quality standards of fishery products produced. In increasing exports of Indonesia's fisheries and marine sector, several strategies are needed, i.e;1) Optimization of the potential of fish resources to increase export activities; 2) Enhance cooperation with other countries and with international institutions related to the production and quality supervision of fishery products; 3) Improved WPP-based national fisheries management; 4) Empowerment and optimization of catches of small fishermen by applying international quality standards; 5) Coaching on handling export standard fishery products; 6) Improvement of infrastructure, facilities, especially to carry out C3Q. 7) Optimization of SLIN system; 8) Increased role of government in maintaining food safety and ecolabelling; 9) Promote the principle of sustainable fisheries management; 10) Establish a special institution to coordinate the implementation of fishery product safety research and risk analysis of fishery products as a basis in determining food safety goals; 11) Synergize between government as a regulator and employers as a executor.